1994
DOI: 10.1159/000310471
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Severity of Normal-Tension Glaucoma in Men and Women

Abstract: To determine whether damage in normal-tension glaucoma is more pronounced in men or in women, we analyzed visual-field damage, intraocular pressure, age, frequency of acral vasospastic reaction on local cooling, and frequency of headache in 28 consecutive patients with newly diagnosed normal-tension glaucoma. The difference between genders with regard to mean visual-field defect was significant (9.4 ± 1.3 dB in men and 6.7 ± 1.0 dB in women; p = 0.034). This difference could not be explained by other variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…1999), which are the main sources of blood supply for the ONH. This may in part explain the coincidence of a disposition to vasospastic reactivity in patients with NTG (Gasser & Flammer 1991; Orgül et al. 1994).…”
Section: Endothelial Dysfunction In Glaucomamentioning
confidence: 98%
“…1999), which are the main sources of blood supply for the ONH. This may in part explain the coincidence of a disposition to vasospastic reactivity in patients with NTG (Gasser & Flammer 1991; Orgül et al. 1994).…”
Section: Endothelial Dysfunction In Glaucomamentioning
confidence: 98%
“…This syndrome is found more frequently in women than men (Flammer and Prunte 1991), which possibly correlates with the observation that normal tension glaucoma (NTG) is twice as common in women. Furthermore, the female gender is considered an independent risk factor for visual fi eld loss progression in NTG (Orgul et al 1994;Drance et al 2001). The increased susceptibility in females may be due to falling estrogen levels, which are known to have a vasoprotective effect and are reduced post-menopause (Siesky et al 2008).…”
Section: Vasospasmmentioning
confidence: 99%
“… 3–6 Caring for loved ones with vision loss is burdensome and often leaves the caregiver exhausted and at risk of health problems. 5 7 8 A UK study 9 showed an elevated level of caregiver burden associated with caring for family with wet AMD, which was equivalent to the burden experienced by caregivers of patients with rheumatoid arthritis and multiple sclerosis, 10 11 and higher than for patients with colorectal cancer. 9 …”
Section: Introductionmentioning
confidence: 99%